Soft Power in Global Politics. Part I. Regional Dimension. The Works of the Round Table - Dar'ya Borisovna Kazarinova (RUDN Journal of Political Science, 2012)
On 5 of June 2012 at the department of comparative politics of the PFUR was held the round table: «Soft power in global politics: regional and functional dimensions”.